2016
DOI: 10.1590/s1984-29612016023
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic meningoencephalomyelitis associated with Myxobolus sp. (Bivalvulidae: Myxozoa) infection in the Amazonian fish Eigenmannia sp. (Sternopygidae: Gymnotiformes)

Abstract: The genus Myxobolus, parasites that infect fishes, which cause myxobolosis, includes spore organisms belonging to the phylum Myxozoa and represents approximately 36% of all species described for the entire phylum. This study describes lymphocytic meningoencephalomyelitis associated with Myxobolus sp. infection in the brain and spinal cord (the central nervous system, CNS) of Eigenmannia sp., from the Amazon estuary region, in the Administrative District of Outeiro (DAOUT), Belém, Pará, Brazil. In May and June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Among myxozoans, freshwater histozoic Myxobolus species are recognized for their strict or high host-organ/tissue specificity [5], infecting a large variety of fishes within a wide geographical range [6][7][8][9]. Regarding pathogenecity, previous studies conducted in South American freshwater fishes reported Myxobolus species to cause considerable pathological alterations such as lymphocytic meningoencephalomyelitis, myocarditis of the heart, perivascular edema in the interlamellar area and deformation and compression of capillaries of the gill lamellae [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Among myxozoans, freshwater histozoic Myxobolus species are recognized for their strict or high host-organ/tissue specificity [5], infecting a large variety of fishes within a wide geographical range [6][7][8][9]. Regarding pathogenecity, previous studies conducted in South American freshwater fishes reported Myxobolus species to cause considerable pathological alterations such as lymphocytic meningoencephalomyelitis, myocarditis of the heart, perivascular edema in the interlamellar area and deformation and compression of capillaries of the gill lamellae [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%